2016
DOI: 10.1103/physreve.94.032132
|View full text |Cite
|
Sign up to set email alerts
|

Directed random walk with random restarts: The Sisyphus random walk

Abstract: In this paper we consider a particular version of the random walk with restarts: random reset events which suddenly bring the system to the starting value. We analyze its relevant statistical properties, like the transition probability, and show how an equilibrium state appears. Formulas for the first-passage time, high-water marks, and other extreme statistics are also derived; we consider counting problems naturally associated with the system. Finally we indicate feasible generalizations useful for interpret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 20 publications
2
76
0
Order By: Relevance
“…As a model of an animal returning to its nest between multiple excursions, the inclusion of resets to a diffusive motion [5] is a first step in the formulation of a model cappable of capturing the global dynamics from the multiple internal states of the animals. After that, multiple papers have been devoted to study many types of processes with different resetting mechanisms , some of them focusing on the completion time of the processes [27][28][29][30], or using the reset to concatenate different processes [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…As a model of an animal returning to its nest between multiple excursions, the inclusion of resets to a diffusive motion [5] is a first step in the formulation of a model cappable of capturing the global dynamics from the multiple internal states of the animals. After that, multiple papers have been devoted to study many types of processes with different resetting mechanisms , some of them focusing on the completion time of the processes [27][28][29][30], or using the reset to concatenate different processes [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…There, a diffusive particle is studied when it may occasionally reset its position with a constant probability and the authors find that a non-equilibrium steady state (NESS) is reached and the mean first passage time of the overall process is finite and attains a minimum in terms of the resetting rate. The existence of a NESS has been further studied for different types of motion and resetting mechanisms [5][6][7][8][9][10][11][12][13][14][15][16][17][18], showing that they are not exclusive of diffusion with Markovian resets. Aside from these, other works have shown that the resetting does not always generate a NESS but transport is also possible when the resetting probability density function (PDF) is long-tailed [19][20][21][22] or when the resetting process is subordinated to the motion [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…This type of process may lead to an optimal resetting rate for the first-passage time as shown for the discrete model in [32], since now a reset does not always represent a penalty for the process: it can help the walker to regain its direction when it has reached a region which is far from its target.…”
Section: Alternate Process With Resetsmentioning
confidence: 99%
“…Furthermore, the possibility of having walkers relocated to a known position [30] or, more specifically, to a previous maximum [31], have been considered. Here we can also find the Sisyphus random walk [32], where a walker with oriented and deterministic step lengths is subject to random resets to the initial point.…”
Section: Introductionmentioning
confidence: 99%